PORTUGUESE VERSION OF THE QUICK MILD COGNITIVE IMPAIRMENT (QMCI-P) SCREEN—RESULTS FROM THE IBIS STUDY. (11th November 2018) - Santos, P; O'Caoimh, R; Paul, C; Molloy, W
Abstract: Background: As health professionals and researchers face more and more older adults and limited assessment times, there has been an increasing demand for shorter sensitive, reliable and valid cognitive screening instruments. Objective: To adapt the Qmci for Portuguese-language countries, to explore concurrent validity against most common short cognitive screening instruments - MMSE-P and MoCA-P and to assess correlations with other neurospychological dimensions. Methods: Demographic and clinical data (cognition, personality, depression and functionality) of older adults aged ≥65, attending ten day care centres (n=113) and residents in two long-term care institutions (n=53), were collected and assessed with short screening tools. Results: 148 individuals were screened with Qmci-P - median age of 77 (IQR +/-15); 64% female. 103 participants completed the assessment battery and those scoring ≥21 on GDS (indicating possible active depression) were excluded (n=11). The final sample (n=93) had a median age of 74 (IQR +/-15), significantly younger than all those initially consenting (p=0.03). Internal consistency of the Qmci-P using Cronbach's Alpha was 0.823, better than with MoCA (0.79) and MMSE (0.54). The median Qmci-P score was 57/100 (IQR +/-26) with a median MoCA of 21/30 (IQR +/-8) and median SMMSE of 27/30 (IQR +/-5). Qmci-P screen scores were strongly, positively and significantly correlated with both MMSE (r=0.61, 95% CI 0.45–0.72, p<0.001) and MoCA (r=0.63, 95% CI 0.36–0.80, p<0.001). Conclusion: The Qmci-P is a valid short cognitive screen. Given the psychometric properties and brevity (3–5 minutes), it may be preferable for use than MMSE (7–8 minutes) and MOCA (10–12 minutes).